2023
DOI: 10.4103/jehp.jehp_581_22
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, knowledge, and psycho-emotional aspect of infertility among women seeking fertility assistance at a tertiary care hospital in Chhattisgarh, a cross-sectional study

Abstract: BACKGROUND: The lack of fundamental knowledge and awareness about the biological process of reproduction is low worldwide but has reportedly higher incidence rates in under-developed countries. Infertility can have a tremendous effect on a woman's psychological and social well-being, pushing her toward mental stress, anxiety, depression self-blame, self-isolation, feeling of worthlessness, and lack of interest in life. The present study was conducted to determine the level of knowledge and awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…В структуре бесплодного брака женское бесплодие, по разным статистическим данным, составляет 40-45%. Столкнувшись с проблемой бесплодия, женщины испытывают серьезное социальное давление со стороны не только семьи, но и общества в целом [1,2]. Вследствие этого они начинают испытывать глубокое психоэмоциональное напряжение, которое усиливается с увеличением продолжительности брака и отсутствием эффекта от получаемого лечения [3][4][5].…”
Section:  введениеunclassified
“…В структуре бесплодного брака женское бесплодие, по разным статистическим данным, составляет 40-45%. Столкнувшись с проблемой бесплодия, женщины испытывают серьезное социальное давление со стороны не только семьи, но и общества в целом [1,2]. Вследствие этого они начинают испытывать глубокое психоэмоциональное напряжение, которое усиливается с увеличением продолжительности брака и отсутствием эффекта от получаемого лечения [3][4][5].…”
Section:  введениеunclassified
“…Studies suggested gynecological hitches causes’ primary and secondary infertility and serves as a reason of decline in matrimonial and social relationships [21] . Similarly, infertility supplemented to the feeling of social isolation and withdrawal [19] .…”
Section: Introductionmentioning
confidence: 99%